Ideal cardiovascular health metrics and the risk of nonalcoholic fatty liver disease in Korean adults - Sun Young Shim; Sun Jae Jung; Seung Up Kim; Hyeon Chang Kim (BMC, 2023)
Abstract Background The association between cardiovascular risk factors and nonalcoholic fatty liver disease (NAFLD) is well established, but whether cardiovascular health (CVH) metrics is associated with NAFLD had not been fully studied. Thus, we examined the association between CVH metrics and NAFLD in the middle-aged Korean population. Methods We used data of 2,928 (851 men and 2,077 women) participants aged 30-64 years from the Cardiovascular and Metabolic Disease Etiology Research Center study. CVH metrics were measured using a modified version of Life's Simple 7 by the American Heart Association. NAFLD diagnosis was based on the fatty liver index or liver-to-spleen ratio on computed tomography. A multiple logistic regression model was used to investigate the cross-sectional and longitudinal associations between CVH metrics and NAFLD. Results In the cross-sectional analysis, the odds ratio for NAFLD was lower in participants with ideal CVH (odds ratio [OR], 0.13; 95% confidence interval [CI], 0.08-0.18), while it was higher in individuals with poor CVH (OR, 2.87; 95% CI, 2.13-3.86). Similarly, the risk of new-onset NAFLD was lower in participants with ideal CVH (OR, 0.28; 95% CI, 0.11-0.74), and higher in individuals with poor CVH (OR, 2.20; 95% CI, 0.50-9.72) in the longitudinal analysis of a subgroup. Conclusions Ideal CVH was associated with a lower risk of NAFLD while poor CVH was associated with a higher risk of NAFLD. These findings suggest that making efforts to encourage people to manage their CVH to the ideal level may prevent and manage NAFLD.